(Des)controle do imaginário: o regime militar como lastro das ficções de Micheliny Verunschk e Joca Reiners Terron - Oliveira, Julia de Mello Silva (2024)
Since the beginning of this second millennium, we have been favoring the improvement of the data-driven way of living. In this improvement, the market is increasingly establishing its logic of speculation and prospecting of demands and agendas by using socially circulating discourses. Through this mechanism, the market can offer to the customers products that fit in their interests until we reach the current peak of the datasphere (BEIGUELMAN, 2021). From the beginning of such improvement until this very moment in which we consolidate it, information is the great driver of profit. The publishing market, which functions as a discursive institution (SALGADO, 2016), utilizes the media-algorithmic rules to speculate and explore the agendas and demands socially in circulation and incorporates them as a basis for the publication, circulation, and sale of books. Indeed, the author is also a result of his time and has a position in this dynamic as a catalyst and prism of culture that appears filtered in his written products. To be published and to the publication have some impact, however, it is necessary to take part in the publishing market dynamics. This is the logic that definitely determines the themes and forms of literature since we began to assume information as an organizational vector of Western thought. In Brazil, we have seen, little by little, a progressive political process that reflects ideologies centralizing issues of equality and social justice. When we had a president who was a former activist against the military dictatorship of 1964 (which coincides with the work of the National Truth Commission and the 50th anniversary of the regime) we were experiencing the peak of information, discourses, and social demands for an inclusive, fair, and diverse democracy, capable of looking at its past, present and future with that very lens. Groups in favor of this ideology and against it are equivalent to groups in favor of historical reparations regarding the various authoritarianism agendas we have experienced since colonization and groups that do not think this should be a value in managing the country's politics. Regardless of the pole - in favor or against it -, the debate was set, and polarized information was in circulation, generating demands to be met by the market and the publishing market. The coincidence between “being in favor of the dictatorship” and “being against such values as guides for State management” or between “being against the dictatorship” and “being in favor of a specific social democracy” had consequences for literature, especially in one of its niches: the 1964 dictatorship literature. In fact, due to the context introduced, this literary segment presented a politicized and referentialized literary representation (which is positive in the sense that literature could be an equalizer of political debate). On the other side, nonetheless, the fiction work was marginalized. This scene - more referentialization, less fiction - made the boom in Brazilian contemporary post-dictatorial novel. This kind of literature has been published since the 2000s and centralizes the 1964 dictatorship in its plot. It also has a tentacular narrative that materializes the aesthetics of insurgency to be put in the form of a literary product (ZOHAR, 2017) which will be neutralized by the need for profit, the end of the entire marketing process. Our work, based on the Theory of Imaginary Control by Luiz Costa Lima (2007; 2009), describes this phenomenon and proves the hypothesis that Noite dentro da noite by Joca Reiners Terron, and Trilogia Infernal, by Micheliny Verunschk, escape such description.